Teacher Effectiveness and Academic Performance of Physics in Secondary Schools in Entebbe Municipality. A Cross-Sectional Study. - Muyodi , Muzamiru; Kamya, Willy (Student's Journal of Health Research Africa, 2022)
Background: The study was about teacher effectiveness and students’ academic performance focusing on Physics in Secondary Schools in Entebbe Municipality. The study was guided by the following objectives; to determine how teacher’s mastery of content and ability to teach affect students’ performance in physics in Secondary Schools in Entebbe Municipality, to determine the performance of students in physics in Entebbe municipality, and to find out if there is a significant relationship between teacher’s effectiveness (teacher’s mastery & ability to teach) and performance in physics in Entebbe municipality. Methodology: A survey research design with quantitative and qualitative research approaches was used, and the data was collected using a questionnaire and interview guide from 100 respondents. Results: The results for objective one indicate a moderate grand mean of 3.40 and a standard deviation of 1.064. The results from objective two show that with a low grand mean of 2.610 and a standard deviation of 0.938. Generally, the findings in objective three on the relationship between Teacher effectiveness and Academic performance of physics revealed that with N=100, P value=0.203 and Sig. 0.005. Conclusion: There is no significant positive relationship between a teacher’s effectiveness and the academic performance of students in physics. Recommendation: The school administration should ensure that the more senior teachers can help the junior ones to learn how to best teach physics, and adopt the use of ICT tools and digital game-based learning to make physics learning, there is a need to employ the techniques of differentiating between students to help them become better performers as individuals and there is need to adopt the use of the flipped classroom model, encourage cooperative learning, effective communication among the teachers and with students, build rapport with the parents/caregivers.